The Correlation Between Mechanical Ventilation Duration, Pediatric Sequential Organ Failure Assessment Score, and Blood Lactate Level in Children in Pediatric Intensive Care - Lu, Fang; Qin, Hua; Li, Ai-Min (Frontiers in Pediatrics, 2022)
Objective: This study aimed to investigate whether the ventilation duration for children undergoing invasive mechanical ventilation (IMV) in pediatric intensive care unit (PICU) is correlated with pediatric sequential organ failure (pSOFA) score, white blood cell (WBC) count, blood lactate level, and duration of fever. Methods: Retrospectively reviewed that the medical records of patients who received IMV in the PICU of Jingzhou Central Hospital between January 2018 and December 2020. According to the duration of IMV in diagnosis-related groups, these patients were divided into two groups: group A, ventilation duration < 96 hours, and group B, ventilation duration ≥ 96 hours. Each group’s pSOFA scores, WBC counts, blood lactate levels, and durations of fever were compared. Logistic regression analysis was used to analyze the clinical risk factors of ventilation duration ≥ 96 hours, and the receiver operator characteristic (ROC) curve was drawn. Results: A total of 42 patients were included, including 23 in group A and 19 in group B. The difference in pSOFA score between group A and group B was statistically significant (P < 0.05), while the differences in blood lactate level, duration of fever, and WBC count between the two groups were not statistically significant (P > 0.05). Logistic regression analysis was conducted to analyze the influencing factors of mechanical ventilation duration ≥ 96 hours. An ROC curve was drawn with pSOFA score as a test variable and duration of mechanical ventilation ≥ 96 hours as a state variable, revealing that the area under the curve was 0.76 (SE = 0.075, 95% CI: 0.614–0.906, P = 0.005). The sensitivity and specificity were 68.4% and 73.9%, respectively, and the corresponding pSOFA score was 7.5. Conclusions: When the pSOFA score ≥ 8, the risk of a duration of mechanical ventilation ≥ 96 hours increases.